Sosialisasi Dan Lomba Masak Kreasi Olahan Ikan Di Desa Sitiwinangun, Cirebon, Jawa Barat - Asya Oktiani; Abdel Rahim Salaby; Mufidah Ghina Zahro; Nadya Karunia Putri; Ammar Abiyu Bassam; Sri Devi; Fany Octaviana; Sofie Dehan Fahlevie; Himawan Haryo Wibisono; Muhammad Aries (Program Studi Gizi UNSIKA, 2021)
Indonesia is an archipelago’s country with abundant ocean resources including high amount of consumable fish species. Fish has good nutritional content, including protein, omega 3 and 6 fatty acids, vitamins, and minerals. This aims of this activity were to improve the knowledge and awareness of public about the importance of consume fish, especially people of Sitiwinangun Village, Jamblang District, Cirebon Regency. The method used is through socialization activities and also a cooking competition of fish dishes. According to this activity, it can be seen that there are still many people who do not know the nutritional content and health benefits of fish. However, many people, especially women who active in Family Welfare Program (PKK), have good skills in cooking fish dishes, even though the dishes are not liked by children in general. Keywords: Fish dishes, creativity, Gemarikan (Gerakan gemar makan ikan)